Efektifitas Metode Quantum Learning Untuk Meningkatkan Motivasi Belajar Siswa - hasbahuddin hasbahuddin (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2020)
The problem examined in this research is whether the quantum learning method is effective in increasing student motivation in SMK 3 Pangkep. This study aims to determine the effectiveness of quantum learning methods to improve student motivation in SMK 3 Pangkep. Data collection techniques in this study used a questionnaire, with a sample of 35 students from all class X with a population of 175 students in SMK Negeri 3 Pangkep. This type of research used in this study is the type of experimental research. The research design used was one group pretest - posttest design. The results showed that there were differences between test results before and after being treated with a quantum learning metode of 0.879 at a significance of 0.879> 0.05. While the value of t arithmetic is smaller than t table (21,707 <2,042) at a significance level of 5% meaning that the quantum learning method is effective to increase student motivation in SMK Negeri 3 Pangkep.